Moral Particularism and the Non-Flatness Requirement - Tuck, Peter (Univerzita Pardubice, 2025)
In this thesis I begin by examining two common assumptions shared by realist metaethical philosophers. Firstly, that ethics requires some explicated, systematic ontological structure, and concomitantly, an epistemology that explains our skill in navigating this structure to actually make ethical decisions. E.g. on moral generalism, there is an identified list of moral principles, and agreed ways of finding out what the principles are, then applying them to decide what to do in any particular situation. I then point out that moral particularism, which is the view that there are no moral principles, has been widely criticised for lacking such a structure, and therefore rendering the metaphysical moral landscape ?flat?. This is called the flattening objection, which leads to the apparently connected claim that particularists therefore cannot provide an epistemology: a way to make specific decisions. Without structure, there can be no related skill, and since they have no structure, they cannot explain skill. On the first point, about structure, I point out that the flattening objection relies on the assumption that what is required is an understanding of the moral landscape as having a global shape. I argue that while it is impossible for us to have knowledge of this global shape, individual decisions, which are themselves always local, only need rely on local shape. And that since particularists actually have a clear concept of local shape, the objection is not fatal, as long as we can provide a clear answer as to how we make reliably correct decisions relying only on local shape. On the second point, about skill, I say that particularists do have a clear epistemological picture of how to relate local structure to moral decision making: the weighing of reasons. I conclude that since their view apparently satisfies the need for local structure and local skill, and that since these are sufficient for successfully navigating moral life, we can discard the common metaethical assumption that global ontologies are required, and therefore, dissolve the flattening objection against moral particularism.
Keywords: morální partikularismus; morální generalismus; zplošťující námitka; kvietismus; morální percepce; vážené důvody; Moral Particularism; Moral Generalism; Flattening Objection; Quietism; Moral Perception; Reason Weights